AMPK and SIRT1 activation contribute to inhibition of neuroinflammation by thymoquinone in BV2 microglia - Velagapudi, Ravikanth (Mol Cell Biochem, 2017)
Thymoquinone is a known inhibitor of neuroinflammation. However, the mechanism(s) involved in its action remain largely unknown. In this study, we investigated the roles of cellular reactive oxygen species (ROS), 5′ AMP-activated protein kinase (AMPK) and sirtuin 1 (SIRT1) in the anti-neuroinflammatory activity of thymoquinone. We investigated effects of the compound on ROS generation in LPS-activated microglia using the fluorescent 2′,7′-dichlorofluorescin diacetate (DCFDA)-cellular ROS detection. Immunoblotting was used to detect protein levels of p40(phox), gp91(phox), AMPK, LKB1 and SIRT1. Additionally, ELISA and immunofluorescence were used to detect nuclear accumulation of SIRT1. NAD(+)/NADH assay was also performed. The roles of AMPK and SIRT1 in anti-inflammatory activity of thymoquinone were investigated using RNAi and pharmacological inhibition. Our results show that thymoquinone reduced cellular ROS generation, possibly through inhibition of p40(phox) and gp91(phox) protein. Treatment of BV2 microglia with thymoquinone also resulted in elevation in the levels of LKB1 and phospho-AMPK proteins. We further observed that thymoquinone reduced cytoplasmic levels and increased nuclear accumulation of SIRT1 protein and increased levels of NAD(+). Results also show that the anti-inflammatory activity of thymoquinone was abolished when the expressions of AMPK and SIRT1 were suppressed by RNAi or pharmacological antagonists. Pharmacological antagonism of AMPK reversed thymoquinone-induced increase in SIRT1. Taken together, we propose that thymoquinone inhibits cellular ROS generation in LPS-activated BV2 microglia. It is also suggested that activation of both AMPK and NAD(+)/SIRT1 may contribute to the anti-inflammatory, but not antioxidant activity of the compound in BV2 microglia.